Should we use driving pressure to set tidal volume?. Issue 1 (February 2017) - Grieco, Domenico L.; Chen, Lu; Dres, Martin; Brochard, Laurent
Abstract : Purpose of review: Ventilator-induced lung injury (VILI) can occur despite use of tidal volume ( V T ) limited to 6 ml/kg of predicted body weight, especially in patients with a smaller aerated compartment (i.e. the baby lung) in which, indeed, tidal ventilation takes place. Because respiratory system static compliance ( C RS ) is mostly affected by the volume of the baby lung, the ratio V T / C RS (i.e. the driving pressure, Δ P ) may potentially help tailoring interventions on V T setting. Recent findings: Driving pressure is the ventilatory variable most strongly associated with changes in survival and has been shown to be the key mediator of the effects of mechanical ventilation on outcome in the acute respiratory distress syndrome. Observational data suggest an increased risk of death for patients with Δ P more than 14 cmH2 O, but a well tolerated threshold for this parameter has yet to be identified. Prone position along with simple ventilatory adjustments to facilitate CO2 clearance may help reduce Δ P in isocapnic conditions. The safety and feasibility of low-flow extracorporeal CO2 removal in enhancing further reduction in V T and Δ P are currently being investigated. Summary: Driving pressure is a bedside available parameter that may help identify patients prone to develop VILI and at increased risk of death. No study had prospectively evaluated whether interventions on Δ P may provide a relevant clinical benefit, but it appears physiologically sound to try titrating V T to minimize Δ P, especially when it is higher than 14 cmH2 O and when it has minimal costs in terms of CO2 clearance.